The importance of DNA replication termination and the MHF complex to genome stability - Neo, J (2015)
The final stages of replication fork termination requires the timely and orderly orchestration of catalytic and enzymatic activities. Given the complexity of this process, it is conceivable that the final stages of fork termination is susceptible to problems that could trigger recombination, which could lead to deleterious genomic rearrangements if ectopic homologous sequences are recombined. Using the site-specific RTS1 barrier in fission yeast, I demonstrated that fork termination is generally not a recombinogenic process, and that hyper-recombination-induced by fork blockage at RTS1 is largely a result of replication fork restart. To investigate the actual mechanisms and proteins, which drive and influence recombination at a replication barrier, I studied the MHF proteins, which assist Fml1 in limiting crossovers during double-strand break (DSB) repair and promoting Rad51-mediated recombination at impeded replication forks, and are also components of the constitutive centromere-associated network (CCAN). Intriguingly, structural studies revealed that the MHF can exist as an octamer in vitro. I examined the biological significance of octameric MHF by employing three mutations that disrupt the octamer configuration in vitro. In fission yeast, these mutations cause hypersensitivity to methyl methanesulfonate (MMS), suggesting that the MHF octamer may have a role in DNA repair. One of the “octamerisation” mutants, exhibits greater hypersensitivity to MMS than the other two, and biochemical experiments indicated that this is because it confers an additional defect in MHF’s interaction with Fml1. Further genetic experiments on this mutant suggest that the ability of Fml1 to unwind D-loops depends more critically on its interaction with MHF than fork reversal. Additionally, I showed a synergistic interaction between Dcr1 and MHF, and demonstrated that in the absence of Dcr1, there is a greater need for recombination to tolerate/repair DNA damage. Lastly, I uncovered a novel function for the MHF in controlling the initiation of septation.